2009
DOI: 10.1002/jez.538
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical composition, lipoperoxidation, Na+/K+ATPase activity and reproduction of Hyalella castroi (amphipoda, dogielinotidae) fed with different diets

Abstract: This study compared the effect of different diets on the biochemical composition (lipids, cholesterol, proteins and glycogen) and the levels of lipoperoxidation and activity of Na(+)/K(+)ATPase of Hyalella castroi. We also investigated some patterns of the life cycle including survival, precopulatory mating pairs and number of ovigerous females after 21 days of culture with different diets. These crustaceans live in limnetic environments of the plateau (1,200 m a.s.l.) of the state of Rio Grande do Sul, in sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…According to Sastry (1983), oogenesis involves an intense biochemical synthesis, with the mobilization of lipids and proteins for egg development. Gering et al (2009), studying the intermediary metabolism of amphipod Hyalella castroi feeding with one diet with animal proteins and other with vegetal proteins in the same proportion, did not verify a different pattern in reproduction which suggests that the type of diet was not important but the concentration. In the present study, we verified that the MFC diet that has adequate protein level improves the reproduction of couples and eggs number.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…According to Sastry (1983), oogenesis involves an intense biochemical synthesis, with the mobilization of lipids and proteins for egg development. Gering et al (2009), studying the intermediary metabolism of amphipod Hyalella castroi feeding with one diet with animal proteins and other with vegetal proteins in the same proportion, did not verify a different pattern in reproduction which suggests that the type of diet was not important but the concentration. In the present study, we verified that the MFC diet that has adequate protein level improves the reproduction of couples and eggs number.…”
Section: Discussionmentioning
confidence: 90%
“…After this intense utilization of glycogen and proteins, there was a decrease in the lipoperoxidation and activity levels of animals, suggesting a decrease in metabolic rate. This suggests that carbohydrate, protein and lipids are all important energy stores, although the lipid reserve may be more important for reproduction, as in other crustaceans including other amphipods (Cruz-Rivera et al, 2000;Cortés-Jacinto et al, 2003;Oliveira et al, 2007;Gering et al, 2009). MCF reversed these metabolic responses, where this diet provided valuable information concerning the maintenance of these animals in the laboratory, for instance for toxicology experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The weight of individuals reared on the 3 different diets was not measured in the present study; however, a previous study done in this laboratory found that there was no significant difference in the weights of the organisms fed the different diets at 42 d old (L. Kennedy, T. Watson‐Leung, unpublished data). Fatty acids are important for egg production and development, as well as being an important energy storage able to be used at times when food conditions may be poor . The breakdown of the fatty acid profiles was not provided in the diet analysis; however, it is likely that the diatoms in the diatom component of the FF‐D diet provided a different fatty acid profile than the other 2 diets, as indicated by the increased reproduction, as well as the increased health of the neonates reared on that diet.…”
Section: Discussionmentioning
confidence: 99%
“…One of the key components in optimizing the health of organisms before testing is ensuring that the diet is able to meet the nutritional and energy requirements of the species. The diet provided to H. azteca in the brood culture is critical, because it can heavily impact the organism's reproductive success, impacting the ability of females to produce eggs and having a critical role in survival and growth within the culture . De March and Othman and Pascoe found that the number of eggs per brood correlated with the size of the female, emphasizing the importance of diet in optimizing the organism's reproductive potential.…”
Section: Introductionmentioning
confidence: 99%
“…The animals were fed a combination of commercial feed for fish and the macrophyte (C. rimosa), presented 351.99 kcal/100 g to total caloric value, as standardize by Gering et al (2009).…”
Section: Collection Of H Castroimentioning
confidence: 99%